"While there is p57, there is hope." The past and the present of diagnosis in first trimester abortions: Diagnostic dilemmas and algorithmic approaches. A review. (December 2021) - Giacometti, Cinzia; Bellan, Elena; Ambrosi, Alessandro; Dei Tos, Angelo Paolo; Cassaro, Mauro; Ludwig, Kathrin
Abstract: Distinction of hydatidiform moles (HM) from non-molar (NM) specimens and subclassification of HM as complete hydatidiform mole (CHM) versus partial hydatidiform mole (PHM) are important for clinical practice and investigational studies. The issue of diagnostic reproducibility is still unsolved, the lack of diagnostic accuracy based on morphology is substantial with an important interobserver variability, even between experienced gynecologic pathologists. Many ancillary techniques have been investigated in the last years to refine HM diagnosis. p57 (a paternally imprinted, maternally expressed gene) immunohistochemistry, based on the unique genetics of CHM (purely androgenetic), PHM (diandric triploid), and NM specimens (biparental, with allelic balance) can identify CHMs, which lack p57 expression because of a lack of maternal DNA. However, although its role in HM diagnosis is pivotal, it does not allow the distinction of PHM from NM specimens, both of which express p57 due to the presence of maternal DNA. Molecular genotyping, which compares villous and decidual DNA patterns to determine the parental source and ratios of polymorphic alleles, distinguishes purely androgenetic CHM from diandric triploid PHM, and both of these from NM specimens. Beyond the claim of establishing a "diagnostic truth", exceptions and peculiar genetic scenarios in the origin of rare CHM and PHM should be kept in mind when approaching any ancillary technique. An algorithmic approach, even in settings with limited resources, can help the pathologists in the diagnostic dilemma of diagnosis of first trimester abortions. Graphical abstract: Image 1 Highlights: Recognition of molar pregnancies is critical for appropriate management (72). Interobserver variability in morphological diagnosis; necessity for ancillary testing (85). Immunohistochemical p57 expression reliably identifies complete hydatitiform moles (83). PCR-based DNA genotyping powerful diagnostic adjunct for accurate classification (80). Diagnostic algorithms for abortion specimens outline strategy for additional testing (84).